Social Media and Educational Development of Youths in Nigeria - Elekwa, Josephine Ebere; Douglas-Chukwu Ozioma (International Journal on Integrated Education, 2022)
Social media is one of the greatest forums that has fast-tracked communications and social development in all walks of life. In the field of education, while some scholars view social media as the learners’ friend some consider it a foe. This study therefore discussed the effect of social media on the educational development of youths in Nigeria. It was discovered that social media is instrumental to the educational development of youths in terms of accuracy in data analysis during research, speedy dissemination of instructions or information, and note taking during lectures. On the other hand, it was discovered that social media leads to addiction among students whereby the youths engaged in endless interaction with their peers on issues that are counterproductive to their studies. Based on these findings, the researchers made some recommendations.